Diversity and Integration or Hannibal Intra Portas? - Matziouri, Apostolia (Advances in Social Sciences Research Journal, 2025)
According to the Old Testament «When the Most High divided the nations, as He scattered the sons of Adam, He set the boundaries of the nations according to the number of the angels of God». (Deuteronomy 32:8-9). Therefore, every mass movement and settlement of people in foreign lands is condemned. Especially, when it has elements of invasion (dictated for example by a specific religion), the deliberate population transfer for demographic alteration, is considered poaching-colonisation and should be condemned under the Article 49 of the Geneva Treaty (1949), the violation of which, results in penal sanctions (Article 146). Even more so, when the inhumane crimes at the expense of the natives committed by the conqueror are equal to war crimes (Article 147). Therefore, we have been in a state of war. But what do the United Nations do about it? They have been always very selective about when to mediate and in favour of whom. What do Western state leaders do? Demonstrations have recently been recorded in various parts of the Western world against illegal immigration as a reaction to the explosion of crime and the alteration of morals, customs, profile and principles of the West, while all that talk that was developed over the past years, trying to blur the image that stood in front of our eyes is no longer convincing. The purpose of this article is not to bridge a gap in the name of a peaceful coexistence but to disillusion by revealing what is behind the curtain and the role played by key people in positions of power and/or in the public eye.